Thermal analysis of glass-fiber reinforced polymer rebars. Issue 3 (3rd July 2017) - Saidova, Zarina; Grakhov, Valery; Yakovlev, Grigory; Gordina, Anastasiya; Zakharov, Andrey
Abstract: The article contains a short overview of current research base state in the field of thermal analysis of glass-fiber reinforced polymer (GFRP). The relationship between temperature raise and specimens weight loss is presented. It is noted that results of experiments run by different scientists vary widely and cannot form a common GFRP behavior model under heating. To compare the effect of thermal exposure on GFRP of a number of Russian manufacturers, the thermal analysis of composite rebar was carried out. Weight fluctuation was recorded with temperature ranging from 22 to 500 °C. The results of visual estimation of the effect of heating GFRP specimen up to 200 °C is also presented. All experiments were conducted according to requirements of corresponding regulations.